2021
DOI: 10.3390/jcm10081611
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Non-Invasive Radiofrequency-Based Diathermy in the Postoperative Phase of Knee Arthroplasty: A Double-Blind Randomized Clinical Trial

Abstract: Total knee replacement (TKR) surgery ameliorates knee function and the quality of life of patients, although 20% still experience dissatisfaction due to pain limiting their function. Radiofrequency Diathermy (MDR) has shown improvements in knee osteoarthritis and patellofemoral pain syndrome. As such, this study aims to assess the effects of MDR in the postoperative treatment of TKR patients. Forty-two participants were allocated to an experimental, placebo, or control group. For two weeks, subjects performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…García-Marín 2021 [ 96 ] studied TKR post-operative pain. All three groups underwent usual physiotherapy (active mobilization, strengthening, and walking), and then one group underwent CRET while the other performed sham CRET.…”
Section: Resultsmentioning
confidence: 99%
“…García-Marín 2021 [ 96 ] studied TKR post-operative pain. All three groups underwent usual physiotherapy (active mobilization, strengthening, and walking), and then one group underwent CRET while the other performed sham CRET.…”
Section: Resultsmentioning
confidence: 99%
“…This method can increase tissue permeability through the use of high-frequency electromagnetic signals. It has been reported to effectively alleviate pain, improve the range of motion, and enhance the quality of life among patients with KOA [ 11 , 21 ]. On the other hand, in clinical studies using a 448 kHz energy transfer through a combination of capacitive and monopolar modes, a reduction in postoperative pain and improvements in gait ability and range of motion have also been reported [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the efficacy of 4.4 MHz RF diathermy in managing pain, such as low back pain and shoulder pain [ 9 , 10 ]. While there have been studies on RF diathermy for KOA, the frequencies applied in each study have varied [ 11 , 12 , 13 , 14 ]. However, there are still not enough prospective studies performed to investigate the effectiveness of 4.4 MHz RF diathermy in treating KOA.…”
Section: Introductionmentioning
confidence: 99%
“…Physical rehabilitation is a common recovery method following body joint surgery (e.g., frozen shoulder, humeral and clavicle fractures, anterior cruciate ligament reconstruction, knee fractures, patellofemoral pain syndrome, and knee arthroplasty [1]). This method aims to achieve complete and satisfactory patient recovery and avoid further complications.…”
Section: Introductionmentioning
confidence: 99%